Analisis Literasi Kimia: Pentingnya Pemahaman Konsep Kimia di Sekolah Menengah - Asri Hanifah Ambarwati; Hurul Aini; Nasywaa Syahra Putri; Nazwa Karin Fadillah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Developing scientific literacy in students is the main objective of any reform in science education. Scientific literacy is one of the most significant competencies of the 21st century. One problem with science education in Indonesia is that students fail to give enough attention to the knowledge that has already been taught, which results in a lack of scientific comprehension. By observing how the student responded to the student's collaboration abilities during their chemical studies from the viewpoint of the chemical literacy teacher, the study was trying to figure out how well second-year students understood chemical literacy on the level of a problem. In order to ascertain high school chemical literacy, a descriptive research design and quantitative methodology were employed in the study. The interview guides and chemical literacy questionnaires, which provide data on students' understanding of chemical literacy, are the study's instruments. Students from high schools in cities and villages, both regular and vocational, are the subjects of the study. Studies show that 39% of respondents agreed that high school students had very little understanding of the concept of chemistry. It is further supported by the opinions of a few of the chemical teachers who teach the XI class.